TINDAK TUTUR DALAM IKLAN DI RADIO SONORA 96.7 FM PONTIANAK - Mulyani, Rida; Amir, Amriani; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was motivated by advertisements which found locus, illocutionary, and perlocution speech found on Sonora Radio 96.7 Fm Pontianak. This study aims to describe the type of speech acts and pragmatic meanings of speech acts used in advertisements on Sonora Radio 96.7 FM Pontianak. This research method is a descriptive method with qualitative research. Data collection techniques were carried out by skillful referencing and note taking techniques. The data in this study were broadcast in advertisements on Sonora Radio 96.7 FM Pontianak. Data sources are advertisements broadcast on Sonora Radio with a research period of October 20 to November 20, 201. Application of data contained on Sonora Radio 96.7 FM Pontianak which is taught ad text with KD 3.4 Reviewing the presentation and linguistic patterns of ad text, slogans , or posters (which make pride and motivation) from various sources that are read and heard. 4.4 Presenting ideas, messages, invitations in the form of advertisements, slogans, or posters verbally and in writing. Based on the results of data analysis, speech acts on Sonora 96.7 FM Pontianak adverts using Austin theory are follow locution, illocutionary and perlocution. And the speech acts that are more dominant according to Searle are expressive speech acts. The implementation of learning in KD 3.4 and 4.4 of students produces text-based advertisements, namely in the form of poster text.Keywords: advertisements, pragmatics, speech acts, Sonora Radio 96.7 FM Pontianak.